USE OF PHOTO EDIT APPLICATION WITH STUDENTS 'BODY IMAGE - Eka Malfasari; Heny Aprilyanti; Yeni Devita; Rina Herniyanti; Ifon Driposwana Putra (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2020)
Body image is an attitude or the conscious and unconscious way a person perceives his body. Editing is the process of organizing, reviewing, selecting, and arranging images and sound from a production recording. This study aims to determine the relationship between the use of photo editing applications and body image among students at STIKes Payung Negeri Pekanbaru. This research method is a quantitative study using a correlation study design and aapproach Cross Sectional Study. This research was conducted at STIKes Payung Negeri Pekanbaru. The sample of this study was 352 respondents using stratified random sampling technique. The instrument used for the variable use of photo editing applications was a guttman scale and for body image variables a Likert scale. The results showed that 65.9% of respondents used photo editing applications and 53.4% ​​of respondents with negative body image. The results of the analysis on 352 respondents obtained a p value of 0.01 <α, namely 0.05 and an OR value of 1.851. It can be concluded that there is a relationship between the use of photo editing applications and body image in students at STIKes Payung Negeri Pekanbaru. Researchers recommend for future researchers to identify what are the bad effects of using photo editing applications on psychological reactions